Portable Chest Radiography Through Glass During COVID-19 Pandemic—Initial Experience in a Tertiary Care Center. Issue 1 (February 2021) - Rai, Archana; Ditkofsky, Noah; Hunt, Bryce; Dubrawski, Margaret; Deva, Djeven; Mathur, Shobhit
Background: Portable chest radiograph for COVID-19 positive patients and persons under investigation can be acquired through glass doors or walls of isolation rooms to limit exposure to the pathogen and conserve resources. Purpose: To report our initial experience with acquiring portable chest radiographs through glass doors of isolation rooms. Methods: Only 1 of 2 radiology technologist team members donned personal protective equipment and stayed inside the isolation room, while the second technologist and the radiography unit remained outside during the procedure. First hundred radiographs acquired through glass at the emergency department of our institute formed the "through glass radiograph" group. Hundred consecutive portable chest radiographs performed in a conventional manner formed the "conventional radiograph" group for comparison. Imaging database and feedback from operations leader were used to identify occurrences of a failed procedure. Suggestion of repeating the study and comments related to quality of the study were recorded from the reports of the staff radiologist. Results: There was no instance of failed acquisition, nondiagnostic examination, or suggestion of repetition in both groups. No significant difference in the number of reports with quality related remarks ( P > .05) was found between the 2 groups. Radiography through glass doors was associated with increased suboptimal positioning related remarks in radiology reports ( P < .05). No significant association was identified among other comments about image quality. Conclusion: Our initial clinical experience suggests that the acquisition of portable chest radiographs through the glass doors of isolation rooms is technically feasible and results in diagnostic quality studies.